2002
DOI: 10.1093/treephys/22.9.661
|View full text |Cite
|
Sign up to set email alerts
|

Neutral lipids and phospholipids in Scots pine (Pinus sylvestris) sapwood and heartwood

Abstract: Variations in the concentration and composition of triacylglycerols, free fatty acids and phospholipids were analyzed in Scots pine (Pinus sylvestris L.) trees at five sites. Disks were taken at breast height or at a height of 4 m from the stems of 81 trees differing in diameter and growth rate. The mean concentration of triacylglycerols in sapwood was 26 mg g(-1) dry mass; however, variation among trees was large (16-51 mg g(dm)(-1)). The concentration of triacylglycerols was slightly larger at 4 m height in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…The storage temperature acts as a catalyst to accelerate the chemical oxidation process. Research studies conducted by Back and Allen [14], Höll and Pieczonka [15], and Piispanen and Saranpä ä [16] on woody biomass (Scots pine and Norway spruce) indicated that triglycerides undergo auto-oxidation in the presence of temperature and emit off-gases like CO and hexanal. Springer and Hajny [34], Kuber et al [35], and Kuber [36,37] have established that auto-oxidation of unsaturated fatty acids and other extractives leads to spontaneous heating of wood chips and sawdust during storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage temperature acts as a catalyst to accelerate the chemical oxidation process. Research studies conducted by Back and Allen [14], Höll and Pieczonka [15], and Piispanen and Saranpä ä [16] on woody biomass (Scots pine and Norway spruce) indicated that triglycerides undergo auto-oxidation in the presence of temperature and emit off-gases like CO and hexanal. Springer and Hajny [34], Kuber et al [35], and Kuber [36,37] have established that auto-oxidation of unsaturated fatty acids and other extractives leads to spontaneous heating of wood chips and sawdust during storage.…”
Section: Discussionmentioning
confidence: 99%
“…These reported CO and CO2 emissions for wood chips and wood pellets are well above the threshold concentration levels established by U.S. Department of Labor Occupational Safety and Health Administration. According to Back and Allen [14], Höll and Pieczonka [15], and Piispanen and Saranpä ä [16], dry woods like Scots pine and Norway spruce contain about 3%-5% triglycerides, which can undergo oxidation and yield hexanal and other off-gases (such as CO). Svedberg et al [11] indicated that in addition to CO, wood pellets also emitted hexanal during storage.…”
Section: Introductionmentioning
confidence: 99%
“…5). Saranpää and Nyberg (1987) Piispanen and Saranpää (2002) reported lipid concentrations in the outer stem sapwood (first 1-2 cm) for P. sylvestris from southern Finland to vary from tree to tree from 1.6 to 5.1% d.m. (mean ca.…”
Section: Discussionmentioning
confidence: 99%
“…The content of stearic acid was comparable in rZ and K. The total content of identified free fatty acids in rZ and K is 1.8-2.5 times higher than in sW (Figure 3). In heartwood (hW) forming species, like pines and black locust, the concentration of free fatty acids is the highest in the hW (Hillinger et al 1996;Piispanen and Saranpää 2002). Similarly to the process of hW formation (Hillinger et al 1996), free fatty acids in the rZ of beech could originate from the hydrolysis of sapwood triacylglycerols.…”
Section: Compoundmentioning
confidence: 99%